Investigating the Operational Limits of a Horizontal Axis Wind Turbine Gearbox Through Unsupervised Comparison Between Units of the Same Equipment from Three Nearby Power Plants - AVILA, S. L.; VELLOSO, B. P.; CARDOZO, G.; MATSUO, T. K. (Advances in Electrical and Computer Engineering, 2025)
Considering the operating limits proposed by ISO 10816-21 – Evaluation of Machine Vibration by Measurements on Non-Rotating Parts – for horizontal-axis wind turbine gearboxes, we analyzed the behavior of nearly one hundred gearboxes from three nearby onshore wind farms (~10 sq km) in northeastern Brazil. Each wind turbine is equipped with an identical mechanical vibration monitoring system, comprising ten sensors and nine features per sensor. First, we assessed whether the equipment operated within the ISO-defined limits. Next, we confirmed the trends detected by the ten gearbox sensors exhibited a strong correlation with one another. However, trends among similar pieces of equipment operating under the same conditions were not strongly correlated. An unsupervised correlation analysis using the Fast Fourier Transform (FFT) was conducted for all wind turbines, considering the zone boundary values proposed by ISO. The unsupervised correlation analysis enhances knowledge for more targeted monitoring, achieving an accuracy score exceeding 70%. This approach contributes to the development of a more effective predictive maintenance program.